Penguasaan PUEBI terhadap Keterampilan Menulis Teks Laporan Hasil Observasi - Poni Ernis; Neneng Wahyuni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between the mastery of PUEBI with the skills of writing text reports on the results of observations. The research method uses correlation with quantitative types. Sampling was done using the cluster random sampling technique. The research instrument is an objective test and a performance test. The results showed that the average value of PUEBI and the value of the observation report were both 76 with good qualifications. The rcount obtained is 0.9030 and tcount 11.3193 with degrees of freedom n-2 (31-2=29), and a significant rate of 0.05. In conclusion, there is a significant relationship between PUEBI and the observation report. Keywords: Writing Observation Report Text, Mastery of PUEBI